Patterns Of Solidarity Of Interned Citizens On The Creativity Of Criminates In Class Iib Cebing-High Corporate Institutions - Helen Siahaan (Trigin Publisher, 2022)
The background is from the desire of the inmates to improve their quality of life while in the Class IIB Tebing-High Correctional Institution. Which in the end will become provisions after being released from prison. So that criminals who are languishing in correctional institutions are no longer people who are passive in serving their prison terms but they are active and together to eliminate the bad stigma about them.The method used in this research is a qualitative method with a descriptive study approach. This research refers to the total institution theory which in the process there is a pattern of socialization, namely primary and secondary socialization. The results of the study stated that solidarity with correctional inmates in self-reliance development activities at the Class IIB Tebing Tinggi institution emerged due to a sense of similarity in sharing the same feelings experienced by all correctional inmates while in the correctional institution which caused them to strive to be better. The solidarity of the inmates in the correctional facility is in the form of the motivation and participation of the inmates who participate in the development of independence to influence the inmates who do not participate in the development of independence. With the solidarity between fellow inmates in prison to jointly participate in self-reliance development activities so that later after leaving the prison, they can have the skills acquired and implemented in the outside world, especially in the world of work. The implementation of this independence development activity cannot be separated from the participation of the employees of the Class IIB Tebing-High Correctional Institution, especially the Sections of the Head of BINADIK and GIATJA of the Class IIB Tebing-High Correctional Institution.